Cardiovascular Effects of Hookah Smoking: Potential Implications for Cardiovascular Risk. Issue 9 (5th April 2018) - Rezk-Hanna, Mary; Benowitz, Neal L
Abstract: Introduction: Smoking is a major cause of cardiovascular morbidity and mortality worldwide. Hookah (ie, waterpipe) smoking is a centuries-old revived yet understudied global epidemic of tobacco use. Because of the traditional set-up of a hookah-pipe, in addition to inhaling tobacco-combustion products, smokers are also exposed to large amounts of charcoal combustion products from the burning charcoal briquettes used to heat the hookah flavored tobacco. Despite being heavily advertised and actively glamorized in the mass media as a healthier tobacco alternative, the toxicological constituents of hookah smoke—including nicotine, carbon monoxide, particulates, oxidants, heavy metals, phenols and flavorants—indicate the potential to cause adverse cardiovascular events. Methods: Herein, we review evidence on hookah smoke toxicological constituents, cardiovascular effects and potential mechanisms by which hookah smoke aerosol could cause cardiovascular disease. Results: The evidence reviewed here indicates that contrary to the widespread popular belief that hookah is a healthier tobacco alternative, the constituents of hookah smoke aerosol contains similar chemicals compared to cigarette smoke, many of which are known to be harmful to cardiovascular health and mediated by similar pathophysiologic processes. Because the burning charcoal briquettes are a unique source of toxicant emissions specific to hookah smoking, some constituents differ in their quantities from cigarettes with some of their cardiovascular effects unknown. Conclusions: To date, much more is known about the constituents and their toxicology than about the effects of hookah smoking on human cardiovascular health. Further research on long-term consequences of hookah use is needed. Implications: This review provides an overview on the potential impact of hookah smoking on cardiovascular health. Readers will gain an insight into evidence on its toxicological constituents, human health effects, and pathophysiological mechanisms by which hookah smoking might cause cardiovascular disease. The review also highlights current research gaps regarding the cardiovascular consequences of hookah smoking, specifically the long-term consequences in the United States and Europe among flavored-hookah tobacco users.